Preparation method of high-strength heat-insulation double-layer ceramic hollow sphere

Through the preparation method of double-layer ceramic hollow spheres, the problem of traditional ceramic hollow spheres being prone to rupture under external pressure or high temperature environments is solved, and the shell wall is thicker, denser, and significantly improved compressive strength is achieved.

CN119462202APending Publication Date: 2025-02-18NORTHEASTERN UNIV CHINA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411662043.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional ceramic hollow sphere preparation methods are difficult to accurately control the wall thickness and internal structure, resulting in easy rupture under external pressure or high temperature environments, limiting its reliability and durability in practical applications.

Method used

The preparation method of double-layer ceramic hollow balls is adopted to prepare the template ball by rolling ball method, and then coat the first ceramic shell layer in the ceramic slurry, and then the second coat and cure are carried out to form the second ceramic layer. shell. The template is then removed by low-temperature calcination and high-temperature sintering to densify the ceramic shell.

Benefits of technology

The double-layer ceramic hollow ball with thicker shell wall, higher density and significantly improved compressive strength is achieved, improving its reliability and durability in practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength heat-insulation double-layer ceramic hollow ball, and aims to overcome the defects of a traditional ceramic hollow ball in the aspects of wall thickness control, density, toughness and heat insulation performance. According to the method, the double-layer ceramic hollow ball with thicker shell wall, higher density and remarkably improved compressive strength is constructed by preparing through a template method and utilizing an accurately controlled template form and removal process. By optimizing the proportion of the ceramic powder, the ceramic fiber, the sintering aid and the adhesive and forming the uniform and compact second shell layer on the surface of the single shell layer, the toughness and the strength of the hollow sphere are enhanced. The prepared double-layer ceramic hollow sphere not only has the characteristics of high strength, high heat insulation performance, good toughness, light weight and the like, but also shows wide application potential in the fields of anti-explosion and anti-penetration composite materials, aerospace, high-temperature heat insulation, catalyst carriers, light structural materials and the like; and a key material support is provided for technical progress and industrial upgrading in related fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of inorganic non-metallic materials, in particular to a method for preparing high-strength heat-insulating double-layer ceramic hollow spheres. Background technology:

[0002] As a high-performance material, composite high-strength ceramic hollow spheres have shown wide application potential in the fields of explosion-proof and anti-penetration composite materials, aerospace, high-temperature insulation, catalyst carriers and lightweight structural materials. However, traditional methods for preparing ceramic hollow spheres, such as sol-gel method, direct foaming method and centrifugal casting method, are difficult to accurately control the wall thickness and internal structure of the hollow spheres, resulting in the hollow spheres being easily broken when subjected to external pressure or high temperature environment, which limits their reliability and durability in practical applications.

[0003] In view of the defects in the above-mentioned background technology, the present invention aims to provide a method for preparing a composite high-strength ceramic hollow sphere, which can prepare a double-layer ceramic hollow sphere with thicker shell wall, higher density and significantly improved compressive strength. Summary of the invention:

[0004] The object of the present invention is to provide a method for preparing a high-strength heat-insulating double-layer ceramic hollow sphere, which specifically comprises the following steps:

[0005] 1. Preparation of template spheres:

[0006] Urea is selected and mixed with fine, uniform and volatile organic powders such as flour, and a ball rolling method is used to make template balls with a diameter of 0.1-3mm, regular shape and uniform size.

[0007] 2. Preparation of double-layer ceramic hollow spheres:

[0008] The template ball is placed in a slurry containing ceramic powder (such as a mixture of one or more powders of Al2O3, SiO2, ZrO3, SiC, Si3N4, BN, B4C, etc.), and the ceramic slurry is evenly coated on the surface of the template ball by a ball rolling machine at a certain speed and angle to form a first ceramic shell layer. After drying and preliminarily curing the first ceramic shell layer, the slurry is coated and cured again to form a second ceramic shell layer, thereby obtaining a double-layer ceramic hollow ball blank.

[0009] 3. Template removal:

[0010] The double-layer ceramic hollow sphere green body is subjected to two stages of low-temperature calcination and high-temperature sintering to remove the template and densify the ceramic shell.

[0011] 4. Performance optimization:

[0012] By adjusting the composition and proportion of ceramic powder, the formula of slurry, sintering process and other parameters, the thermal insulation performance, compressive strength and toughness of double-layer ceramic hollow spheres can be further optimized. The introduction of additives such as zirconium oxide or yttrium oxide, combined with a double-layer shell structure, can effectively improve the thermal insulation performance of hollow spheres. Description of the drawings:

[0013] Figure 1 It is a schematic diagram of the physical structure of the spherical shell-containing fiber-containing alumina hollow sphere prepared in Example 1 of the present invention.

[0014] Figure 2 It is a schematic diagram of the internal structure of the hollow alumina sphere with a spherical shell and fibers prepared in Example 1 of the present invention.

[0015] Figure 3 This is the Weibull distribution diagram of the compressive strength of a single alumina hollow sphere prepared in Example 1 of the present invention.

[0016] Figure 4 It is a schematic diagram of the structure of the double-layer spherical shell hollow ball prepared in Example 3 and Example 4 of the present invention. Specific implementation method:

[0017] The present invention is further described in detail below with reference to the accompanying drawings and specific examples, but the protection scope of the present invention is not limited to the described contents.

[0018] Example 1

[0019] A hollow alumina ceramic sphere with a spherical shell containing fibers is prepared by the following steps:

[0020] 1. Take 10kg of alumina powder with a particle size of 10-100μm, 0.05-0.1kg of fly ash and 0.2-0.8kg of one or two of alumina fiber, silica fiber or mullite fiber with a length of 100-500μm and put them into a planetary ball mill. Set the ball milling speed to 60-80 rpm and the mixing time to 3-5h to obtain mixed powder 1.

[0021] 2. Urea powder with a particle size of 100-300 μm and flour with a particle size of 100-200 μm are evenly mixed in a mass ratio of 5:3 to form mixed powder 2. At the same time, 1 / 10 of the total mass of the mixed powder is taken out of water, and the mixed powder is repeatedly sprayed with water through a ball making equipment and rolled to form micro beads.

[0022] 3. Select micro beads with a size of 0.5-0.8 mm as seeds.

[0023] 4. Add the screened template microspheres into a rotating coating machine with a speed set to 50-100 rpm, and then add 4wt.% polyvinyl alcohol aqueous solution and mixed powder 1 every five minutes for 5-10 times. The ratio of hollow spheres, polyvinyl alcohol binder and mixed powder 1 is 10:1:20 (mass ratio).

[0024] 5. Screen alumina ceramic balls with internal template balls with a size of 0.8-1.2mm.

[0025] 6. Raise the temperature of the alumina ceramic ball from room temperature to 350°C at a heating rate of 5°C / min and keep it for 30-50h (the organic seeds are decomposed and carbonized to form a hollow and remove the binder. The extension of the debinding time will significantly reduce the pore content and pore size inside the spherical shell). Then, maintain the heating rate of 10°C / min to the sintering temperature of 1800°C and keep it for 3h. After the sintering reaction is completed, cool it to room temperature at a cooling rate of 10°C / min. The sphere has an appearance diameter of 0.8-1.2mm, a hollow diameter of 0.5-0.8mm, a wall thickness of 0.3-0.5mm, and a bulk density of 1.35-1.50g / cm 3 Spherical particles, single particle compressive strength is 60100N, the appearance and internal wall thickness of the prepared alumina hollow spheres are shown in the attached Figure 1 and attached Figure 2 As shown in the figure, the alumina ceramic hollow spheres have uniform size, smooth and dense surface, and the static compressive Weibull distribution of a single alumina hollow sphere is shown in the attached figure. Figure 3 shown.

[0026] Example 2

[0027] A hollow alumina ceramic sphere with a spherical shell containing fibers is prepared by the following steps:

[0028] 1. Take 10kg of alumina powder with a particle size of 10-100μm, 0.05-0.1kg of fly ash and 0.2-0.8kg of one or two of alumina fiber, silica fiber or mullite fiber with a length of 100-500μm and put them into a planetary ball mill. Set the ball milling speed to 60-80 rpm and the mixing time to 3-5h to obtain mixed powder 1.

[0029] 2. Urea powder with a particle size of 100-300 μm and flour with a particle size of 100-200 μm are evenly mixed in a mass ratio of 5:3 to form mixed powder 2. At the same time, 1 / 10 of the total mass of the mixed powder is taken out of water, and the mixed powder is repeatedly sprayed with water through a ball making equipment and rolled to form micro beads.

[0030] 3. Screen microbeads with a size of 0.1-0.2 mm as seeds.

[0031] 4. Add the screened template microspheres into a rotating coating machine with a speed set to 50-100 rpm, and then add 4wt.% polyvinyl alcohol aqueous solution and mixed powder 1 every five minutes for 5-10 times. The ratio of hollow spheres, polyvinyl alcohol binder and mixed powder 1 is 10:1:20 (mass ratio).

[0032] 5. Screen alumina ceramic balls with internal template balls of size 0.15-0.3mm. Raise the temperature of the alumina ceramic balls from room temperature to 350°C at a heating rate of 5°C / min and maintain it for 30-50h, then maintain the heating rate of 10°C / min to the sintering temperature of 1800°C and keep it for 3h. After the sintering reaction is completed, cool it to room temperature at a cooling rate of 10°C / min. The spheres have an external diameter of 0.15-0.3mm, a hollow diameter of 0.1-0.2mm, a wall thickness of 0.05-0.1mm, and a bulk density of 1.45-1.55g / cm 3 Spherical particles, single particle compressive strength is 20-50N.

[0033] Example 3

[0034] A ceramic double-layer hollow sphere particle is realized by the following steps:

[0035] 1. Take 10kg of silicon carbide powder with a particle size of 10-100μm, 0.05-0.1kg of one or both of boron powder or carbon powder and 0.2-0.8kg of one or both of carbon fiber and silicon carbide fiber with a length of 100-500μm and put them into a planetary ball mill. Set the ball milling speed to 60-80 rpm and the mixing time to 3-5h to obtain mixed powder 1.

[0036] 2. Urea powder with a particle size of 100-300 μm and flour with a particle size of 100-200 μm are evenly mixed in a mass ratio of 5:3 to form mixed powder 2. At the same time, 1 / 10 of the total mass of the mixed powder is taken out of water, and the mixed powder is repeatedly sprayed with water through a ball making equipment and rolled to form micro beads.

[0037] 3. Select micro beads with a size of 2-3.5 mm as seeds.

[0038] 4. Add the screened template microspheres into a rotating coating machine with a speed set to 50-100 rpm, and then add 4wt.% polyvinyl alcohol aqueous solution and mixed powder 1 every five minutes for 5-10 times. The ratio of hollow spheres, polyvinyl alcohol binder and mixed powder 1 is 10:1:20 (mass ratio).

[0039] 5. Screen silicon carbide ceramic balls with internal template balls with a size of 2.3-3.8 mm.

[0040] 6. Transfer the ceramic balls to a forced air drying oven and keep them at 80°C for 5-8 hours.

[0041] 7. Place 250g of silicon carbide ceramic template with a particle size of 2.3-3.8mm into the coating machine, and then add 10mL of polyvinyl alcohol aqueous solution binder to the ceramic ball template. After that, turn on the coating machine and adjust the speed to 50r / min. Use a stirring tool to fully stir the template during rotation so that the binder is in full contact with the outer surface of all templates. After the binder is in full contact with the outer surface of the hollow ceramic ball, add 150g of yttrium oxide with a particle size of 50-100μm (containing 0.1-0.5% magnesium oxide powder of the same particle size) at one time to cover and bond the ceramic powder to the surface of the ceramic ball as efficiently as possible. Keep the equipment rotating at 50r / min for 5min.

[0042] 1. Place the double-layer ceramic ball containing the template ball inside under inert atmosphere protection (nitrogen or argon), raise the temperature from room temperature to 350℃ at a heating rate of 5℃ / min and keep it for 30-50h, then maintain the heating rate of 10℃ / min to the sintering temperature of 2000℃ and keep it for 3h. After the sintering reaction is completed, cool it to room temperature at a cooling rate of 10℃ / min. The sphere has an external diameter of 2.5-4mm, a hollow diameter of 2-3.5mm, a silicon carbide shell wall thickness of 0.3-0.5mm, a yttrium oxide shell wall thickness of 0.1-0.2mm, and a bulk density of 1.4-1.6g / cm 3 Spherical particles, single particle compressive strength is 150-250N, the prepared double-layer hollow ball example is shown in the attached figure Figure 4 shown.

[0043] Example 4

[0044] A ceramic double-layer hollow sphere particle is realized by the following steps:

[0045] 1. Take 10kg of alumina powder with a particle size of 10-100μm, 0.1-0.3kg of fly ash and 0.3-0.5kg of one or two or three of alumina fiber, silica fiber or mullite fiber with a length of 100-500μm and put them into a planetary ball mill. Set the ball milling speed to 60-80 rpm and the mixing time to 3-5 to obtain mixed powder 1.

[0046] 2. Urea powder with a particle size of 100-300 μm and flour with a particle size of 100-200 μm are evenly mixed in a mass ratio of 5:3 to form mixed powder 2. At the same time, 1 / 10 of the total mass of the mixed powder is taken out of water, and the mixed powder is repeatedly sprayed with water through a ball making equipment and rolled to form micro beads.

[0047] 3. Select micro beads with a size of 0.5-1 mm as seeds.

[0048] 4. Add the screened template microspheres into a rotating coating machine with a speed set to 50-100 rpm, and then add 4wt.% polyvinyl alcohol aqueous solution and mixed powder 1 every five minutes for 5-10 times. The ratio of hollow spheres, polyvinyl alcohol binder and mixed powder 1 is 10:1:20 (mass ratio).

[0049] 5. Screen alumina ceramic balls with internal template balls with a size of 0.7-1.2 mm.

[0050] 6. Transfer the ceramic balls to a forced air drying oven and keep them at 80°C for 5-8 hours.

[0051] 7. Put 150g of alumina ceramic template with a particle size of 0.7-1.2mm into the coating machine, and then add 10mL of polyvinyl alcohol aqueous solution binder to the ceramic ball template. After that, turn on the coating machine and adjust the speed to 50r / min. Use a stirring tool to fully stir the template during rotation so that the binder is in full contact with the outer surface of all templates. After the binder is in full contact with the outer surface of the hollow ceramic ball, add 100g of zirconium oxide with a particle size of 50-100μm (containing 3% yttrium oxide with the same particle size and 0.2% alumina or cerium oxide powder with the same particle size) at one time to cover and bond the ceramic powder to the surface of the ceramic ball as efficiently as possible. Keep the equipment rotating at 50r / min for 5min.

[0052] 2. The double-layer ceramic ball containing the template ball is heated from room temperature to 350°C at a heating rate of 5°C / min and maintained for 30-50h, then heated to sintering temperature 1800°C at a heating rate of 10°C / min and kept at that temperature for 3h. After the sintering reaction is completed, it is cooled to room temperature at a cooling rate of 10°C / min. The sphere has an external diameter of 1.2-1.8mm, a hollow diameter of 0.5-1mm, an alumina shell wall thickness of 0.3-0.5mm, an yttrium oxide shell wall thickness of 0.1-0.2mm, and a bulk density of 1.40-1.65g / cm 3 Spherical particles, single particle compressive strength is 150-200N, the prepared double-layer hollow ball example is shown in the attached figure Figure 4 shown.

Claims

1. A method for preparing high-strength heat-insulating double-layer ceramic hollow spheres, characterized in that: The following steps are involved: (1) Preparation of template spheres: urea is mixed with fine, uniform and easily volatile organic powders such as flour, and a rolling ball method is used to prepare template spheres with a diameter of 0.1-3 mm, regular shape and uniform size; (2) Preparation of ceramic mixed powder: using a high-efficiency ball mill, under suitable temperature and humidity conditions, fully grinding the ceramic powder, ceramic fiber, sintering aid and mixed raw materials to ensure that each component is evenly dispersed to form a fine and uniform ceramic mixed powder; the ceramic fiber is one or a combination of two or three of carbon fiber, silica fiber, glass fiber, basalt fiber, mullite fiber, alumina fiber and silicon carbide fiber; (3) Construction of a double-shell structure: placing a template ball as a seed into a ball-making device, repeatedly spraying a polyvinyl alcohol mixture on the surface of the microsphere, and forming a uniform and dense single-shell ceramic microsphere on the surface of the seed by precisely controlling the spraying speed and the amount of powder added; screening out single-shell ceramic microspheres with a size of 0.2-3.5 mm, drying and placing them into the ball-making device again; after spraying the polyvinyl alcohol mixture on the surface of the microsphere, adding a certain amount of ceramic mixed powder, and forming a composite ceramic microsphere with a double-shell structure by precisely controlling the spraying and powder addition amount; (4) High temperature calcination: placing the double-shell composite ceramic microspheres into a kiln for high temperature calcination to remove the template balls and organic matter and form a preliminary ceramic structure; then calcining the ceramic microspheres at high temperature to promote the ceramicization process and form a dense ceramic structure; during the high temperature calcination process, the temperature is raised to 350°C and maintained for 30-50 hours to remove organic matter and the template, then the temperature is raised to a sintering temperature of 1600-2000°C and maintained for 2-4 hours, and then cooled to room temperature at a cooling rate of 5-15°C / min; (5) Performance optimization: During the calcination process in step (4), zirconium oxide or yttrium oxide powder is introduced into the surface of the double-shell composite ceramic microspheres to improve the thermal insulation performance of the hollow spheres by vapor deposition or infiltration.

2. The method for preparing high-strength heat-insulating double-layer ceramic hollow spheres according to claim 1, characterized in that: In the step (1), the mass ratio of urea powder to flour is 5:3, and 1 / 10 of the total mass of the mixed powder is added during mixing, and the microbeads are produced by repeatedly spraying water and adding the mixed powder through a ball making device to roll and form microbeads.

3. The method for preparing high-strength heat-insulating double-layer ceramic hollow spheres according to claim 1, characterized in that: In the step (2), the ceramic powder is one or more of alumina powder, silica powder or silicon carbide powder; and the sintering aid is one or more of fly ash, boron powder or carbon powder.

4. The method for preparing high-strength heat-insulating double-layer ceramic hollow spheres according to claim 1, characterized in that: In the step (3), the mass ratio of the hollow spheres, the polyvinyl alcohol binder and the ceramic mixed powder is 10:1:15-25.

5. The method for preparing high-strength heat-insulating double-layer ceramic hollow spheres according to claim 1, characterized in that: In the step (5), the particle size of the introduced zirconium oxide or yttrium oxide powder is 10-100 μm, and it may contain 0.1-0.5% magnesium oxide powder and 0.1%-0.3% aluminum oxide or cerium oxide powder of the same particle size as sintering aids.

6. The high-strength heat-insulating double-layer ceramic hollow sphere prepared by the method for preparing the high-strength heat-insulating double-layer ceramic hollow sphere according to any one of claims 1 to 5, characterized in that: The hollow sphere has uniform wall thickness, high density, high strength, good toughness and excellent heat insulation performance.

Citation Information

Patent Citations

  • High-strength and low-density ceramic hollow ball and preparation method thereof

    CN102557594A

  • Method for producing porous heat-insulation ceramic by adopting zirconia hollow spheres

    CN107805065A

  • Preparation method of three-phase ceramic fiber composite heat insulation tile

    CN112125649A

  • Lightweight ceramic ball and preparation method thereof

    CN115385671A

  • High-precision silicon nitride ceramic microsphere, and preparation method therefor and use thereof

    WO2023071897A1